Pelatihan Pengelolaan Sampah Rumah Tangga yang Bernilai Ekonomi di Desa Gelogor Lombok Barat - Herawati Khotmi; Fachrozi; Zulkarnaen; Yusi Faizathul Octavia; I Made Murjana (Edujavare Publishing, 2023)
There are many types of waste, including organic or household waste, plastic waste, and paper waste. Sometimes, even rarely among us, we can manage waste that has economic value. Analysis of the problem situation faced by Gelogor Village, namely that there is no orderly sorting of organic, paper, and plastic waste, they do not understand waste management procedures, the products made still need to have a brand, and difficulties in marketing the products. The aim of this service is to provide training related to waste management that can have economic value in Gelogor Village. The Participatory Action Research (PAR) method was implemented and implemented in three stages: planning, implementation, assessment, and monitoring. The method used is to conduct a field survey first, followed by coordinating the implementation of the service, distributing invitations to the community, preparing a schedule of service activities, and the core activity, namely conducting training. The results of this service research are that Gelogor residents are very enthusiastic about waste management, this can be seen from the various questions asked by the Gelogor Village community. There is great hope for the role of village officials to provide support related to waste management, such as the trash basket in each local resident's house consisting of three trash cans.